0473 The impact on treatment adherence of adding a bedpartner to CBT-I: preliminary findings from a randomised controlled trial (Project REST). (25th May 2022) - Drummond, Sean; Jenkins, Melissa; Mellor, Alix; Norton, Peter; Baucom, Donald; Bei, Bei
Abstract: Introduction: Cognitive Behavioural Therapy for Insomnia (CBT-I) includes often difficult-to-implement behavioural change, and this can result in poor adherence to treatment recommendations. In other CBTs, adding a significant other to "individual" therapy increases adherence. Here, we report preliminary findings from a randomised controlled trial (RCT) of a newly developed partner-assisted CBT-I. Methods: 117 adults with DSM-5 Insomnia Disorder (age M±SD=47.9±15.3yrs; 73F) and their live-in partners participated in a single-blind parallel RCT. They were assigned 1:1:1 to 7wk individual CBT-I (Ind-CBTI), partner-assisted CBT-I (PA-CBTI), or sleep management control (CTRL) conditions. Participants completed daily sleep diary throughout the intervention. Adherence in CBT-I conditions was assessed for Sleep Restriction Therapy (deviation from bed and wake times, naps) and Stimulus Control Therapy (wake time-in-bed during daytime, overnight, and after final morning awakening). Intention-to-treat, mixed effects models examined differences in adherence for "Build" (initial phase to build sleep debt) and "Maintain" (starting the first week when sleep opportunity was titrated upwards) stages of therapy. Results: All conditions showed significant increase in sleep efficiency (p<.001), with significantly faster increase in Ind-CBTI and PA-CBTI compared to CTRL (ps<.001). Sleep Restriction Therapy: Build stage (vs Maintain) had greater adherence to prescribed wake time (p=.045); Condition by Stage interaction (p=.010) showed PA-CBTI (vs Ind-CBTI) adhered better in avoiding naps during Build (vs Maintain). Stimulus Control Therapy: PA-CBTI (vs Ind-CBTI) adhered better to avoiding daytime wake time-in-bed (p=.017), especially during Build (interaction p=.071); Condition by Stage interaction (p=.017) showed PA-CBTI (vs Ind-CBTI) adhered better to avoiding overnight wake time-in-bed during Maintain (vs Build). Both conditions had better adherence to avoiding daytime and wake time-in-bed after final awakening during Maintain (vs Build) Stage (ps<.001). Conclusion: Adherence to CBT-I includes multiple indicators showing distinct features as the intervention progresses across different stages. Aspects of adherence appear modifiable, and adding bedpartners to CBT-I improved adherence to specific aspects of the intervention (i.e., avoiding naps, daytime wake time-in-bed, overnight wake time-in-bed). The Build and Maintain stages of treatment appear to be associated with better adherence to different aspects of the intervention (Sleep Restriction Therapy and Stimulus Control Therapy, respectively). Support (If Any): NHMRC grant APP1105458 (SPAD, DHB, PJN), APP1140299 (BB)Trial registration: ACTRN12616000586415